Green Peopleism: A study Factors that Persuade People to buy Green Products: Understanding the Factors Influencing Indian Consumers' Preference for Green Products (Journal of Advances and Scholarly Researches in Allied Education, 2022)
The environmental effects of goods have become an issue of concern for both manufacturersand consumers. Many consumers and businesses are taking notice of the environmental benefits ofitems like low-power-consumption (energy-efficient) devices, organic foods, lead-free paints, recyclablepaper, and phosphate-free detergents. In recent years, there has been a gradual uptick in interest in thegreen marketing idea in India. There have been a number of green marketing studies done globally, butnot nearly as much academic work has been done on how Indians perceive and value green products.The factors that influence consumers' decisions to purchase green products are dissected here. Here,analyze the responses to a questionnaire designed to elicit information on consumers' attitudes aboutgreen marketing strategies and the items they end up buying as a result. Based on an analysis of 150respondents' opinions, this study discovered a favorable correlation between the availability of ecolabeleditems and people's desire to reduce their environmental impact. Customers' preference for ecofriendlyproducts was shown to be independent of both price and gender.